Sex-Specific Effects of Acute Ethanol Exposure on Locomotory Activity and Exploratory Behavior in Adult Zebrafish (Danio rerio) - Vossen, Laura E.; Brunberg, Ronja; Rådén, Pontus; Winberg, Svante; Roman, Erika (Frontiers in Pharmacology, 2022)
The zebrafish (Danio rerio) is an established model organism in pharmacology and biomedicine, including research on alcohol use disorders and alcohol-related disease. In the past two decades, zebrafish has been used to study the complex effects of ethanol on the vertebrate brain and behavior in both acute, chronic and developmental exposure paradigms. Sex differences in the neurobehavioral response to ethanol have been reported for humans and rodents, yet they remain largely uninvestigated in zebrafish. Although most zebrafish studies did use populations containing both sexes, results were almost always pooled. Here, we show for the first time that male zebrafish of the AB strain display more severe behavioral impairments than females for equal exposure concentrations. Adult zebrafish were immersed in 0, 1 or 2% (v/v) ethanol for 30 minutes, after which behavior was individually assessed in the zebrafish Multivariate Concentric Square Field™ arena. Males exposed to 2% ethanol showed clear signs of sedation, including reduced activity, increased shelter seeking and reduced exploration of shallow zones. The 1% male group displayed effects in the same direction but of smaller magnitude; this group also explored the shallow areas less, but did not show a general reduction in activity nor an increase in shelter seeking. By contrast, 1 and 2% exposed females showed no alterations in explorative behavior. Females exposed to 2% ethanol did not display a general reduction in activity, rather activity gradually increased from hypoactivity to hyperactivity over the course of the test. This mixed stimulatory/depressant effect was only quantifiable when locomotory variables were analyzed over time and was not apparent from averages of the whole 30-minute test, which may explain why previous studies failed to detect sex-specific effects on locomotion. Our results emphasize the importance of explicitly including sex and time as factors in pharmacological studies of zebrafish behavior. We hypothesize that the lower sensitivity of female zebrafish to ethanol may be explained by their greater body weight and associated larger distribution volume for ethanol, which may render lower brain ethanol concentrations in females.